Environmental evolution of coastal afforestations: management strategies for dune fixation in the sandy barriers of Buenos Aires, Argentina - Isla, Federico Ignacio (2022)
Tourism in the southern sandy temperate barriers has historically been one of the drivers of coastal development in Buenos Aires, Argentina. This process, which hasbeen accompanied by dune fixation and a subsequent urbanization, began in the 1930s and occurred in the absence of coastal management policies causing several environmentalproblems. This work aims to analyze the historical development of two dune afforestation projects with the objective of characterizing their main environmental issues. These projects,which started almost simultaneously, are currently at completely different levels of development. For this purpose, a literature and relevant legislation review was carried out, allowingus to characterize them and generate comparisons. At the same time, it is intended to propose new strategies for dune fixation. One of the peculiarities of these afforestation projectsis that two brothers carried them out: Carlos and Ernesto Gesell. Carlos initiated an afforestation that led to the sprawl of Villa Gesell. This city reached historical records of urbangrowth and it is actually one of the most popular bathing resorts of Argentina. Ernesto founded Dunamar on a more restricted dune field and it is currently at a significantly lowerstage of development than Villa Gesell. Coastal erosion, surface runoff increase, decrease of foredune areas and replacement of native dune vegetation are some of the reportedproblems. Currently, there are projects for the expansion of the urban area of these villages under different strategies for dune stabilization. Although their effects have been extensivelydocumented, they propose fixations with fast-growing exotic species. This work proposes the revegetation by means of native species corresponding to the original landscape of thedunes of about a century ago. To this end, certain aspects must be taken into account within the framework of integrated coastal management.